Evaluation of ELISA, RPLA, and Vero cell assays for detecting Clostridium perfringens enterotoxin in faecal specimens. Issue 4 (April 1988) - Berry, P R; Rodhouse, J C; Hughes, S; Bartholomew, B A; Gilbert, R J
Abstract : Three hundred and ninety two faecal specimens from 70 separate outbreaks of suspected Clostridium perfringens food poisoning were examined by enzyme linked immunosorbent assay (ELISA), reversed passive latex agglutination (RPLA), and Vero cell assays for the presence of enterotoxin. Although the most time consuming method, ELISA was the most specific and reproducible. RPLA was slightly more sensitive than ELISA, but it showed some non-specific reactions. The Vero cell assay was the least sensitive and least reproducible method, being affected by some non-specific cytotoxic and cytotonic reactions. Normal rabbit serum should be included in the Vero cell assay as a control for the neutralisation of cytotoxic effects.